Evaluate: $$\int^{\frac{\pi}{2}}_0 \frac{\cos^2x\,dx}{\cos^2x+4\sin^2x}$$

First approach :

$$\int^{\frac{\pi}{2}}_0 \frac{\cos^2x\,dx}{\cos^2x+4(1-\cos^2x)}$$

$$=\int^{\frac{\pi}{2}}_0 \frac{\cos^2xdx}{4 - 3\cos^2x}$$

$$=\int^{\frac{\pi}{2}}_0 \frac{1}{3}\{\frac{4-3\cos^2x-4}{4 - 3\cos^2x}\}\,dx$$

$$=\int^{\frac{\pi}{2}}_0 \frac{1}{3}\{ 1- \frac{4}{4 - 3\cos^2x}\}\,dx$$

$$=\int^{\frac{\pi}{2}}_0 \frac{1}{3} 1\,dx- \int^{\frac{\pi}{2}}_0 \frac{1}{3} \frac{4\sec^2x}{4\sec^2x - 3}\,dx$$

$$=\int^{\frac{\pi}{2}}_0 \frac{1}{3} 1\,dx- \int^{\frac{\pi}{2}}_0 \frac{1}{3} \frac{4 \sec^2x}{4(1+\tan^2x) - 3}\,dx$$

Now I can easily put $\tan x = t$ and I get $\sec^2x \,dx =dt$

Second approach :

$$\int^{\frac{\pi}{2}}_0 \frac{\cos^2x\,dx}{\cos^2x+4\sin^2x}$$

Dividing numerator and denominator by $\cos^2x$ we get :

$$=\int^{\frac{\pi}{2}}_0 \frac{dx}{1 +4\tan^2x}$$

$$=\int^{\frac{\pi}{2}}_0 \frac{dx}{(4)\{\frac{1}{4} +\tan^2x\}}$$

$$=\int^{\frac{\pi}{2}}_0 \frac{dx}{(4)\{\{\frac{1}{2}\}^2 +(\tan x)^2\}}$$

Can we apply this formula of integral here :

$$\int \frac{1}{a^2+x^2}dx = \frac{1}{a}\tan^{-1}\frac{x}{a}$$

I tried but its not working here, I think doing some manipulation we can implement this here.. Please suggest thanks...

  • $\begingroup$ No. that formula won't help in this situation because you have a function in place of $x$ and the $dx$ doesn't correspond to $\tan x$ as it is supposed to in the formula. $\endgroup$ – Paras Khosla Jan 22 '19 at 8:35

Use the fact that

$$3 \int_0^{\pi/2} dx \frac{\cos^2{x}}{\cos^2{x}+4 \sin^2{x}} = 3 \int_0^{\pi/2} dx \frac{\cos^2{x}}{4-3 \cos^2{x}} = 4 \int_0^{\pi/2} \frac{dx}{4-3 \cos^2{x}} - \int_0^{\pi/2} dx$$

So consider the first integral on the RHS:

$$4 \int_0^{\pi/2} \frac{dx}{4-3 \cos^2{x}} = 2 \int_0^{2 \pi} \frac{dy}{5-3 \cos{y}}$$

We may evaluate this latter integral using residue theory. Let $z=e^{i y}$, $dy = -i dz/z$ so that

$$2 \int_0^{2 \pi} \frac{dy}{5-3 \cos{y}} = -i 4 \oint_{|z|=1} \frac{dz}{10z-3(z^2+1)}$$

The denominator has zeroes at $z=1/3$ and $z=3$; of these, only $z=1/3$ lies within the unit circle. Thus the integral is

$$(i 2 \pi) \frac{-i 4}{10-6 (1/3)} = \pi$$


$$\int_0^{\pi/2} dx \frac{\cos^2{x}}{\cos^2{x}+4 \sin^2{x}} = \frac{\pi-(\pi/2)}{3} = \frac{\pi}{6}$$


Alternatively, you may substitute $t=\tan{(y/2)}$, $dy = 2 dt/(1+t^2)$, $\cos{y} = (1-t^2)/(1+t^2)$, and then

$$2 \int_0^{2 \pi} \frac{dy}{5-3 \cos{y}} = \int_0^{\infty} \frac{dt}{(1/4)+t^2} = \frac{\pi}{2} 2 = \pi$$


You multiply and divide by $\sec^{4}(x)$ and see if it's working. The denominator becomes $$\sec^{2}(x) + 4 \tan^{2}(x) \sec^{2}(x)$$ Now use $1+\tan^{2}(x)=\sec^{2}(x)$.


  • In numerator you have $\sec^{2}(x)$

  • In denominator you have $\sec^{2}(x) \cdot \left(1+4\tan^{2}(x)\right) = (1+\tan^{2}(x))\cdot(1+4\tan^{2}(x))$.

  • Now put $t=\tan(x)$ and your integral becomes $$\int_{0}^{\infty} \frac{dt}{(1+t^{2}) \cdot (1+4t^{2})} = \int_{0}^{\infty} \left\{ \frac{1}{1+t^2} -\frac{4}{1+4t^2}\right\} \ dt$$

Oh. I missed a trick here. Note that you had $$\int_{0}^{\pi/2} \frac{dx}{1+4\tan^{2}(x)}$$ Now put $t = \tan(x)$. Then you have $dt = \sec^{2}(x) \ dx $ and so $dx = \frac{dt}{(1+t^{2})}$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.